Las presencias también tienen ausencias: Un auxilio del alma. - LAMAS ARAYA, GIULIANA PAZ (Nomadías)
This article focuses on the literary figure of Gabriela Mistral, a Chilean poet whose life and work illuminate that exhausting emotional burden. Through an analysis of the poem "Palabras Serenas" (Serene Words), taken from her first book, Desolation (1922), from the section "Dolor a su sombra" (Pain in her Shadow), which displays languages of freedom that emerge from subjectivity. From its first publication at the Instituto de las Españas, Mistral raised her firm voice in the face of prevailing pain, hopelessness, a change of perspective, but also a path of light. Her long career, marked by solitude and hope, resulted in the Nobel Prize for Literature (1945). This brief study proposes subjective reading of a select work.